Bureaucratic rents and life satisfaction - Simon Luechinger; Stephan Meier; Alois Stutzer (Institute for the Study of Labor (IZA), 2006)
The monopoly position of the public bureaucracy in providing public services allows government employees to acquire rents. Those rents can involve higher wages, monetary and non-monetary fringe benefits (e.g. pensions and staffing), and/or bribes. We propose a direct measure to capture the total of these rents: the difference in reported subjective well-being between bureaucrats and people working in the private sector. In a sample of 38 countries, we find large variations in the extent of rents in the public bureaucracy. The extent of rents is determined by differences in institutional constraints and correlates with perceptions of corruption. We find judicial independence to be of major relevance for a tamed bureaucracy.
Keywords: D72; D73; I31; J30; J45; K42; H11; H83; 330; public sector; rents; life satisfaction; corruption; judicial independence; Öffentliche Verwaltung; Beamte; Rent Seeking; Korruption; Schätzung; Bürokratietheorie; Europa; Lateinamerika; Lebenszufriedenheit